Guided University Debate (GUD): A new promising teaching and learning strategy for undergraduate nursing students. (October 2016) - Merida, David; Baratas, Ion; Arrue, Marta
Highlights: It is a satisfactory tool for the acquisition of the desired competencies. The GUD stimulates independent learning, reflection and critical thinking. It helps to bridge the gap between clinical practice and classroom practice. GUD can be used as a teaching tool in a systematic manner in Nursing.